Stroke Prevention: Managing Modifiable Risk Factors - Silvia Di Legge; Giacomo Koch; Marina Diomedi; Paolo Stanzione; Fabrizio Sallustio (Stroke Research and Treatment)
Prevention plays a crucial role in counteracting morbidity and mortality related to ischemic stroke. It has been estimated that 50% of stroke are preventable through control of modifiable risk factors and lifestyle changes. Antihypertensive treatment is recommended for both prevention of recurrent stroke and other vascular events. The use of antiplatelets and statins has been shown to reduce the risk of recurrent stroke and other vascular events. Angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin II receptor blockers (ARBs) are indicated in stroke prevention because they also promote vascular health. Effective secondary-prevention strategies for selected patients include carotid revascularization for high-grade carotid stenosis and vitamin K antagonist treatment for atrial fibrillation. The results of recent clinical trials investigating new anticoagulants (factor Xa inhibitors and direct thrombin inhibitors) clearly indicate alternative strategies in stroke prevention for patients with atrial fibrillation. This paper describes the current landscape and developments in stroke prevention with special reference to medical treatment in secondary prevention of ischemic stroke.